(untitled) (Research, Society and Development, 2023)
Blackberry leaves (Morus nigra) are used in menopause to relieve hot flashes and night sweats and have been investigated in metabolic disorders. However, few studies investigated its effects on metabolic and behavioral disorders when associated with menopause. This study evaluated the effects of a hydroalcoholic extract of M. nigra leaves (MN) on body composition, glucose tolerance, and depression and anxiety-like behaviors in ovariectomized rats. For this purpose, 36 female Wistar rats were divided into groups: C – control; COvx – ovariectomized; MNOvx – ovariectomized and given MN at 400 mg.kg-1 body mass/day. Body composition was assessed by DEXA, glucose tolerance by the oral glucose tolerance test, and depression and anxiety-like behaviors by the forced swimming and elevated plus maze tests, respectively. Food intake and body mass gain were higher for MNOvx, followed by COvx and C (p<0.05). The MNOvx group gained less body fat than COvx (p<0.05) and was more glucose tolerant compared to C and COvx (p<0.05). In the elevated plus maze, COvx and MNOvx remained for less time in the open arms and longer in the closed arms than C (p<0.05). In forced swimming, immobility time was higher for COvx, followed by C and MNOvx (p<0.05). The MN protected ovariectomized rats from body fat gain, improved glucose tolerance, and attenuated depression-like behavior. Phytoestrogens and other bioactive compounds in MN may be involved in these effects.